ECONOMIC AND MATHEMATICAL TOOLS FOR ASSESSING THE FEASIBILITY OF CREATING INDUSTRIAL INNOVATIVE SOLVATES - L. G. Matveeva; T. A. Ovsyannikova; E. V. Kaplyuk; E. А. Likhatskaya (Новые технологии, 2022)
The study substantiates the importance of an objective quantitative assessment of the feasibility of creating innovative alliances (solvates) in the industry of the region as the basic platform for structural reform of the national economy especially in the current conditions of a large scale crisis caused by the unprecedented pressure of the collective West on Russia. The purpose of the research is to develop recommendations for the use of intelligent tools of decision support for the rational use of the resources by the participants on the basis of the analysis of theoretical concepts and approaches to the formation of innovative alliances (solvates) in the industry of the region, taking into account their specifics and functional role in the circular process of creating new values. The methodological basis of the research is the convergence of resource-targeted (synchronization of potential sizes with goals) and systemic-synergetic approaches. Methods of scientific analysis and synthesis, economic and mathematical modeling, BigData have been used in the research. The information basis of the research has been formed using official information from the Federal State Statistics Service, as well as data from internal reporting of industrial enterprises. It has been determined that in complex transformational processes that reflect the new economic policy of the state, it is necessary to objectively assess the possibilities of solvates in the industry of a particular region, as well as to identify the reasons for underutilization of their potential. It has been substantiated that the successful implementation of the functions of managing the distribution (between the solvate participants) and the rational use of the resource potential of the association is largely associated with the objectivity of the analysis of the potential effect that can be produced by various forms of interaction. Model tools for assessing the feasibility and effectiveness of various options for organizing production and technological interactions of participants based on the principles of circularity and inclusiveness have been proposed.